OP0051 Dipeptidyl-Peptidase-4 (DPP4) Characterizes A Subpopulation of Fibrosis-Promoting Fibroblasts and Is A Molecular Target for The Treatment of Fibrosis. (15th July 2016) - Soare, A.M.; Dees, C.; Zhang, Y.; Liang, R.; Wohlfahrt, T.; Rauber, S.; Lin, N.; Chen, C.-W.; Ramming, A.; Distler, O.; Mihai, C.; Schett, G.; et al.
Abstract : Background: Dipeptidyl-peptidase-4 (DPP4/CD26) has been recently identified as a marker for a special fibroblast lineage responsible for the tissue remodeling during physiological wound healing. Fibrotic disease may be considered as a consequence of persistent, exaggerated and uncontrolled tissue repair processes. Systemic sclerosis (SSc) is associated with the highest mortality among the connective tissue disorders and effective antifibrotic therapies are still lacking. DPP4 inhibitors are already used in treatment of diabetes. Objectives: The aim of the study was to characterize the DPP4 positive cells, investigate the expression of DPP4 in SSc skin and to evaluate the antifibrotic effect of DPP4 inhibitors in preclinical models of systemic sclerosis. Methods: Mouse fibroblasts were isolated and DPP4 positive cells characterized by fluorescence activating cell sorting. Expression of DPP4/CD26 in human and murine skin was analyzed by immunofluorescence. DPP4 inhibitors were tested in two different concentrations administered orally (Sitagliptin 3mg/kg/d and 10mg/kg/d, Vildagliptin 1, 5mg/kg/d and 15mg/kg/d) in bleomycin induced skin fibrosis and in sclerodermatous chronic graft-versus-host disease mouse model (cGvHD). The antifibrotic effect on skin was assessed by hydroxyproline assay, alpha smooth muscle cells quantification and measuring the dermal thickness. Inflammatory infiltrate was assessed by CD45 immunofluorescence staining. Results: We have demonstrated that DPP4/CD26 positive cells are a unique population of cells implicated in fibrosis. DPP4/CD26 positive cells were increased not only in experimental fibrosis, but also in skin biopsies from SSc patients as compared to healthy volunteers. Treatment with DPP4 inhibitor reduced dermal thickness in both mouse models (p<0.05). The differentiation of resting fibroblasts into myofibroblasts was also significantly decreased (p<0.05) in all treatment groups. Hydroxyproline content of the skin diminished by 40% in comparison with NaCl injected mice or syngeneic transplanted mice. Moreover, DDP4 inhibitors reduced the inflammatory infiltrate in a dose dependent manner in the bleomycin injected skin. Conclusions: DPP4/CD26 identifies a subpopulation of fibrosis-promoting fibroblasts that plays a key role in the pathogenesis of fibrosis in SSc. Moreover, inhibitors of DPP4 show a significant antifibrotic effect in several mouse models of SSc in well tolerated doses. These results may have direct clinical implications as DPP4 inhibitors are already in clinical use for diabetes. Acknowledgement: AS received an EULAR Scientific Training Bursary (2014) and was an Articulum Fellow (2015). Disclosure of Interest: None declared